Digital Finance, Financing Constraint and Enterprise Financial Risk - Zhaolin Wang (Journal of Mathematics)
With the rapid development of the digital economy, digital finance, as a financial innovation combining Internet information technology with traditional finance, plays an essential role in the financial risk of microenterprises and macroeconomic operations. In this paper, the digital financial inclusion index at the provincial level is matched with the microdata of listed companies in Shanghai and Shenzhen stock markets. And, the panel data from 2011 to 2020 are set up from the theoretical and empirical analysis of digital finance on the impact of enterprise financial risk and its mechanism. Firstly, the development of digital finance in China has significantly reduced enterprise financial risk. In order to control the endogeneity, the Bartik instrumental variable is used to select the instrumental variable. Secondly, financing constraint is the function mechanism of digital finance to reduce enterprise financial risk. Thirdly, for enterprises with low debt levels and enterprises located in the eastern region, digital finance plays a more critical role in reducing financial risk.